Comparison of intragastric pressure between endotracheal tube and supraglottic airway devices in laparoscopic hepatectomy: A randomized, controlled, non-inferiority study. Issue 24 (18th June 2021) - Ahn, Jin Hee; Jeong, Ji Seon; Kang, Se Hee; Yeon, Ji Eun; Cho, Eun A.; Choi, Gyu Sung; Kim, Jong Man; Kim, Gaab Soo
Abstract: Background: Supraglottic airway (SGA) devices do not definitively protect the airway from regurgitation of gastric contents. Increased gastric pressure and long operation time are associated with development of complications such as aspiration pneumonia. The aim of this study was to compare intragastric pressure between second-generation SGA and endotracheal tube (ETT) devices during long-duration laparoscopic hepatectomy. Methods: A total of 66 patients was randomly assigned to 2 groups; 33 patients each in the ETT and SGA groups. Intragastric pressure was continuously measured via a gastric drainage tube with a three-way stopcock connected to the pressure monitoring device. Normal saline was added to the end of the gastric drainage tube at each operation time point. Results: Intragastric pressure during pneumoperitoneum was no different between the 2 groups ( P  = .146) or over time ( P  = .094). The mean (standard deviation [SD]) pH of the SGA tip measured after operation was 6.7 (0.4), and a pH <4 was not observed. Relative risk of postoperative complications was significantly higher in the ETT group relative to the SGA group (sore throat, 5.5; cough, 13.0). Conclusions: Use of SGA devices does not further increase intragastric pressure, even during prolonged upper abdominal laparoscopic surgery. Also, the frequency of postoperative sore throat and cough was significantly lower when the second-generation SGA device was used.